OVULATION INDUCTION AGENTS AND OVARIAN CANCER - Barbara Požlep; Helena Meden Vrtovec (Zdravniški Vestnik, 2001)
Background. Ovarian cancer is the most frequent cause of death among gynecologic malignancies. Epidemiological data show that environmental, hormonal and genetic factors are etiologically significant. Beside the already known risk factors, ovulation induction agents have been reported as risk factors in literature since 1986. Over the last two decades, ovulation induction agents have been widely used in various assisted reproduction techniques (ART). This study focused on the question whether in patients receiving ovulation induction agents the risk for developing pathologic processes on the ovaries was higher than in those not receiving them, and whether they were related to the dose and type of ovulation induction agent. Methods. In a prospective study 380 subjects were enrolled. The study group consisted of 280 women who had undergone an ART procedure three or more times. The control group consisted of 120 infertile women, never included in an ART procedure. All the enrolled subjects underwent the same examinations: a detailed gynecological history was taken, pelvic examination and vaginal ultrasound were performed, and a blood sample for tumour marker CA 125 determination was taken. Statistical analysis was done using Chi-square test, t test and logistic regression. Results. Ultrasound examination revealed pathology on the genital tract in 136 women in the study group and in 60 women in the control group. Differences in the incidence of ovarian, tubal and uterine pathology were not statistically significant. The analysis of the medical records showed that the incidence of ovarian pathology was significantly higher in the study than in the control group (p < 0.05). We found no correlation between the incidence of ovarian pathology and type or dose of ovulation induction agent. Increased CA 125 levels were found in 12 women. In none of the women neither malignant nor borderline malignant disease was found. Conclusions. Although the analysis of the data from medical history showed statistically higher incidence of ovarian pathology in the study than in the control group, clinical, ultrasound and biochemical examinations of the current health status showed no difference between the groups. Also, no correlation between ovarian pathology and type or dose of ovulation induction agent was found. We believe that the risk of ovarian malignancy due to ovulation induction agents is very small. For definitive answers large prospective studies are required.